Wave-absorbing agent, non-magnetic wave-absorbing material containing wave-absorbing agent, and preparation method and application of non-magnetic wave-absorbing material
By using BaTiO3/MWCNTs composite and nano-MnO2-loaded absorber in non-magnetic absorbing materials, combined with paraffin matrix, the impedance matching is optimized, and the problems of difficulty in impedance matching and poor absorption performance of low-frequency bands in the prior art are solved, and efficient electromagnetic wave absorption performance is achieved.
Patent Information
- Application Number
- CN202411917082.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
AI Technical Summary
In actual application, existing non-magnetic wave absorbing materials are difficult to match impedance, which easily leads to increased reflection loss and weak magnetic loss capability, making it difficult to achieve effective electromagnetic wave absorption in low frequency bands.
The BaTiO3/MWCNTs composite is used as the absorber and nano MnO2 is loaded on its surface. By adjusting the MWCNTs filling amount, the ratio of absorber and paraffin, and the recombination of nano MnO2 and BaTiO3 with different morphology, the impedance matching is optimized.
The non-magnetic wave absorbing material can achieve an effective absorption bandwidth of up to 4 GHz and a minimum reflection loss of -74.06 dB at a thickness of 4.75 mm, which significantly improves the electromagnetic absorption performance.
Smart Images

Figure CN119799279A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to a wave absorbing agent, a non-magnetic wave absorbing material containing the same, and a preparation method and application thereof. Background Art
[0002] In the existing technology, non-magnetic absorbing materials generally adopt technical means such as adjusting the dielectric constant and conductivity of the material, composite material and structure design, doping and modification, nano-sizing and surface modification. The current status of technological development in this field shows the characteristics of diversified material systems, high performance, environmental friendliness and sustainable development, and expansion of application fields.
[0003] In order to improve the electromagnetic wave absorption efficiency of non-magnetic absorbing materials, related technologies have applied structural design, doping modification, material composite and other methods to make improvements. However, the impedance matching of the resulting non-magnetic absorbing materials is more difficult in practical applications, which easily leads to increased reflection losses, and the magnetic loss capacity is weak, making it difficult to achieve effective electromagnetic wave absorption in the low frequency band, and the electromagnetic absorption performance is not good.
[0004] Therefore, there is an urgent need for a non-magnetic absorbing material with good electromagnetic absorption performance. Summary of the invention
[0005] In view of this, the present application provides an absorbent, a non-magnetic absorbent material containing the same, and a preparation method and application thereof, to solve the problem of how to improve the electromagnetic absorption performance of the non-magnetic absorbent material.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a wave absorbing agent, including a BaTiO3 / MWCNTs composite, and nano-MnO2 loaded on the surface of the BaTiO3 / MWCNTs composite.
[0007] Preferably, the nano-MnO2 is sea urchin-shaped nano-sheet a-MnO2 and / or nano-rod-shaped β-MnO2.
[0008] In a second aspect, the present application provides a method for preparing a wave absorbing agent, comprising the following steps: S1. Under alkaline conditions, an aqueous solution of Ba(OH)2·8H2O and an alcohol solution of (C4H9O)4Ti are mixed to obtain a mixed solution; the mixed solution is mixed with multi-walled carbon nanotubes and polyethylene glycol and subjected to a hydrothermal reaction to obtain a BaTiO3 / MWCNTs composite; S2. Add KMnO4 to the alcohol solution of BaTiO3 / MWCNTs composite, carry out secondary hydrothermal reaction, wash and dry to obtain the absorbent.
[0009] Preferably, the temperature of the first hydrothermal reaction is 120-150°C, and the reaction time is 3-5h; the temperature of the second hydrothermal reaction is 180-200°C, and the reaction time is 6-10h; the mass ratio of Ba(OH)2·8H2O to (C4H9O)4Ti is (0.25-0.3):(0.25-0.3), and the mass ratio of BaTiO3 / MWCNTs to KMnO4 is 2:(1-1.2).
[0010] In a third aspect, the present application provides a non-magnetic wave absorbing material comprising paraffin and a wave absorbing agent.
[0011] Preferably, the mass ratio of paraffin wax to absorber is (5-8):(2-5).
[0012] Preferably, it is a coaxial ring structure, and the thickness of the coaxial ring is 4-5 mm.
[0013] Preferably, the mass of MWCNTs accounts for 5-20% of the non-magnetic absorbing material.
[0014] In a fourth aspect, the present application provides a method for preparing a non-magnetic wave-absorbing material, which is obtained by mixing paraffin wax with a wave-absorbing agent and then pressing the mixture.
[0015] In a fifth aspect, the present application provides an application of a non-magnetic absorbing material under 2-18 GHz conditions.
[0016] The beneficial effects of this application are as follows: This application achieves impedance matching optimization by compounding non-magnetic materials, changing the MWCNTs filling amount, the ratio of absorber to paraffin, and compounding nano-MnO2 with different morphologies (sea urchin-like nanosheets a-MnO2, nanorod-like β-MnO2) and BaTiO3. The prepared non-magnetic absorbing material can achieve an effective absorption bandwidth of 4 GHz and a minimum reflection loss of -74.06 dB at a thickness of 4.75 mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 XRD spectra of different BaTiO3 / MWCNTs / MnO2 materials; Figure 2 This is the XPS spectrum of BaTiO3 / MWCNTs / MnO2 of one embodiment of the present application; Figure 3 TEM and HRTEM images of the BaTiO3 / MWCNTs / MnO2 composite material according to an embodiment of the present application. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The present application provides a wave absorbing agent, including a BaTiO3 / MWCNTs composite, and nano-MnO2 loaded on the surface of the BaTiO3 / MWCNTs composite, which is expressed as BaTiO3 / MWCNTs / MnO2 in this article.
[0020] In some embodiments, the nano-MnO2 is sea urchin-like nanosheets a-MnO2 and / or nanorod-like β-MnO2.
[0021] In this embodiment, the composite of nano-MnO2 with different morphologies (sea urchin-like nanosheets α-MnO2, nanorod-like β-MnO2) and BaTiO3 can achieve impedance optimization, and the mechanism is as follows: 1. Effect of morphology on conductivity and charge transport The urchin-like nanosheets α-MnO2 and nanorods β-MnO2 have different morphological characteristics, which affect the surface area, contact points and conductivity of the material. The urchin-like morphology of α-MnO2 usually has a larger specific surface area and more surface active sites, which helps to improve the interface contact with BaTiO3 and improve the efficiency of interfacial charge transfer; the nanorod-like structure of β-MnO2 usually has strong directionality and high longitudinal conductivity, which allows it to provide a better charge transfer path in the composite material; the conductivity optimization brought about by this morphological difference can effectively adjust the conductivity of the composite material, thereby optimizing its electrical impedance characteristics.
[0022] 2. Interface effect and enhanced charge separation In BaTiO3 and nano-MnO2 composites, the interface effect is the key factor affecting impedance optimization. The interface contact mode and charge transfer path of MnO2 with different morphologies and BaTiO3 are different; the urchin-like nanosheet α-MnO2 has more particle boundaries and pores due to its urchin-like structure, which can form more contact points with BaTiO3, which helps to improve the charge migration efficiency at the interface, reduce the interface resistance, and optimize the charge separation; the nanorod-like β-MnO2 can provide a longer charge transfer path due to the long axis direction of its nanorod-like structure, improve the conductivity of the material, and enable the charge to flow more smoothly in the composite material. Nano-MnO2 with this structure can produce better interface charge separation with BaTiO3 and reduce the overall impedance of the material.
[0023] 3. Composite effect and impedance matching BaTiO3 is a material with a high dielectric constant, which can play an electric field regulating role in composite materials. When combined with nano-MnO2, the morphological characteristics of nano-MnO2 (such as surface energy and specific surface area) can effectively regulate the dielectric response of BaTiO3, improve the dielectric properties of the material, and thus optimize the electrical impedance. The sea urchin-like α-MnO2 can improve the dielectric response matching with BaTiO3 and increase the dielectric constant of the composite material by increasing the surface activity and contact points of the material; the nanorod-like β-MnO2 may improve the conductivity and migration efficiency of the charge, so that the material presents a lower impedance at a specific frequency, further optimizing the performance of the composite material.
[0024] 4. Pseudocapacitive effect of MnO2 MnO2, as a material with pseudocapacitive properties, can adsorb and release charges in the electrochemical process, enhancing the ability to store and release charges. MnO2 with different morphologies exhibits different pseudocapacitive effects: Due to its large specific surface area, the urchin-like nanosheet α-MnO2 can provide more charge storage sites and enhance its pseudocapacitive effect. After compounding, this effect can effectively adjust the electrical impedance of the composite material, especially at high frequencies, it can reduce the electrical impedance; nanorod-like β-MnO2 can provide more electron transmission channels due to its longer structure, which helps to improve the charge transfer efficiency of the composite material, reduce resistance, and thus optimize impedance in the low-frequency region.
[0025] 5. Improvement of electromagnetic wave absorption performance When applied to electromagnetic wave absorption or shielding, the impedance matching of materials is the key, and the impedance of composite materials is closely related to the propagation characteristics of electromagnetic waves. The composite of MnO2 with different morphologies and BaTiO3 can improve the electromagnetic wave absorption performance of the material; the unique morphology of sea urchin-like α-MnO2 may produce a stronger local enhancement effect of the electric field, further improving the composite material's ability to absorb electromagnetic waves, thereby optimizing its impedance matching; the structure of nanorod-like β-MnO2 helps scatter and multiple reflections of electromagnetic waves, enhancing the electromagnetic wave absorption performance of the composite material and improving its impedance.
[0026] The present application provides a method for preparing a wave absorbing agent, comprising the following steps: S1. Under alkaline conditions, an aqueous solution of Ba(OH)2·8H2O and an alcohol solution of (C4H9O)4Ti are mixed to obtain a mixed solution; the mixed solution is mixed with multi-walled carbon nanotubes and polyethylene glycol and subjected to a hydrothermal reaction to obtain a BaTiO3 / MWCNTs composite; S2. Add KMnO4 to the alcohol solution of BaTiO3 / MWCNTs composite, carry out secondary hydrothermal reaction, wash and dry to obtain the absorbent.
[0027] The mechanism of the preparation method of the wave absorbing agent of the present application is as follows: In step S1, Ba 2+ It reacts with Ti(O)4 to form BaTiO3, and generates nanostructures under hydrothermal conditions. At the same time, MWCNTs and PEG are added to improve the dispersibility and stability of the material. The obtained BaTiO3 / MWCNTs composite powder is dispersed in anhydrous ethanol to form a uniformly dispersed solution, in which Ba(OH)2·8H2O provides Ba 2+ ions, KOH increases the alkalinity of the solution and promotes Ba 2+ ions react with other reactants. Titanium tetrabutoxide is relatively stable in alcohol solvents and can effectively provide Ti source. Adding MWCNTs (multi-walled carbon nanotubes) and polyethylene glycol (PEG) can improve the dispersion and uniformity of the composite material. MWCNTs, as a conductivity enhancer, provide an electronic conductive path, and polyethylene glycol helps to control the morphology and dispersion of the particles. In step S2, after KMnO4 is dissolved in the ethanol solution, Mn 2+ Ion, Mn in KMnO4 2+ Under hydrothermal conditions, it is reduced to MnO2, which is uniformly deposited and loaded onto the surface of the BaTiO3 / MWCNTs composite material to form a MnO2 loading layer.
[0028] In some embodiments, the temperature of the first hydrothermal reaction is 120-150°C, and the reaction time is 3-5h; the temperature of the second hydrothermal reaction is 180-200°C, and the reaction time is 6-10h; the mass ratio of Ba(OH)2·8H2O to (C4H9O)4Ti is (0.25-0.3):(0.25-0.3), and the mass ratio of BaTiO3 / MWCNTs to KMnO4 is 2:(1-1.2).
[0029] In this embodiment, by limiting the temperature and time of the secondary hydrothermal reaction, the obtained nano-MnO2 has two forms: sea urchin-like nanosheets a-MnO2 and nanorod-like β-MnO2.
[0030] The present application provides a non-magnetic wave absorbing material, comprising paraffin and a wave absorbing agent.
[0031] In the present application, paraffin wax acts as a matrix material in the non-magnetic absorbing material, playing the role of bonding, stabilizing and adjusting the shape of the non-magnetic absorbing material.
[0032] In some embodiments, the mass ratio of paraffin wax to absorber is (5-8):(2-5).
[0033] In this embodiment, a paraffin ratio that is too high or too low will have different degrees of influence on the electromagnetic properties of the absorbing material. A high ratio will dilute the effective components of the absorbing material, resulting in poor absorbing performance and possibly affecting the stability and durability of the material; while a low ratio will reduce the adhesion of the material, resulting in structural instability, processing difficulties and performance degradation; therefore, the present application reasonably adjusts the paraffin ratio to balance various requirements on the basis of ensuring the electromagnetic properties and mechanical properties of the absorbing material.
[0034] In some embodiments, the mass of MWCNTs accounts for 5-20% of the non-magnetic absorber material.
[0035] In some embodiments, the thickness is 4-5 mm.
[0036] The present application provides a method for preparing a non-magnetic wave-absorbing material. The method comprises mixing paraffin wax with a wave-absorbing agent and pressing the mixture into a coaxial ring.
[0037] The present application provides an application of a non-magnetic wave absorbing material under 2-18 GHz conditions.
[0038] The non-magnetic absorbing material of the present application utilizes the excellent conductivity and dielectric properties of MWCNTs, and is compounded with sea urchin-shaped nanosheets a-MnO2, nanorod-shaped β-MnO2 and BaTiO3, and impedance matching optimization is achieved by combining electromagnetic parameters. The non-magnetic absorbing material prepared using the absorbent exhibits excellent electromagnetic wave absorption performance in the X-band.
[0039] The present solution is further described below through specific embodiments.
[0040] Example 1 A method for preparing a wave absorbing agent comprises the following steps: S1. Weigh 0.271g Ba(OH)2·8H2O (molecular weight 315.48) and 0.672g KOH and dissolve them in 30 mL water to obtain mixed solution A. Place the mixed solution in an ultrasonic cleaner and stir for 15 min. Use a dropper to draw 0.293g (C4H9O)4Ti and add it to 30mL n-butanol. Stir and mix well to obtain mixed solution B. Then mix the two solutions together. Add MWCNTs and 20ml polyethylene glycol to the solution. After ultrasonic stirring for a period of time, transfer the solution to a 100 mL polytetrafluoroethylene reactor and perform hydrothermal reaction at 120°C for 3h. After the reaction is completed, wash the product with deionized water and anhydrous ethanol for several times and vacuum dry it at 60°C for 6h to obtain a black powder BaTiO3 / MWCNTs composite. S2. Weigh 0.2g of the prepared BaTiO3 / MWCNTs powder and ultrasonically disperse it in 60mL of anhydrous ethanol solution. Then weigh 0.1g of KMnO4 and add it to the mixed solution. After stirring for one hour, transfer the mixed solution to a 100mL polytetrafluoroethylene (PPL) reactor and place it in a constant temperature vacuum drying oven at 180°C for hydrothermal reaction for 6 hours. After the reaction is completed, the reaction solution is naturally cooled to room temperature, washed with deionized water and anhydrous ethanol for several times, and vacuum dried at 60°C to obtain an absorbent.
[0041] Embodiment 2-4 A method for preparing a non-magnetic absorbing material comprises mixing an absorber and paraffin in a mass ratio of 8:2, and pressing the mixture into coaxial rings with thicknesses of 5.0 mm, 1.9 mm, and 1.5 mm, respectively, to obtain the non-magnetic absorbing material, wherein the mass of MWCNTs is 5%, 10%, and 20% of the non-magnetic absorbing material (the sum of the mass of the absorber and the paraffin), respectively.
[0042] Embodiment 5-7 A method for preparing an absorbent comprises mixing the absorbent and paraffin wax in a mass ratio of 7:3, and pressing the mixture into coaxial rings with thicknesses of 4.85 mm, 4.75 mm, and 1.5 mm, respectively, to obtain a non-magnetic absorbent material, wherein the mass of MWCNTs is 5%, 10%, and 20% of the non-magnetic absorbent material (the sum of the mass of the absorbent and the paraffin wax), respectively.
[0043] Comparative Example 1 A method for preparing a non-magnetic wave absorbing material, the other contents are the same as those of Example 1, except that BaTiO3 / MWCNTs / MnO2 is replaced by BaTiO3.
[0044] Test and Evaluation The XRD spectra of 5 wt % BaTiO3 / MWCNTs / MnO2, 10 wt % BaTiO3 / MWCNTs / MnO2, and 20 wt % BaTiO3 / MWCNTs / MnO2 are shown in Figure 2. Figure 1As shown in the figure, a diffraction peak is observed at about 2θ=45°, indicating that the sample has a cubic crystal structure. At different MWCNTs filling amounts, in the BaTiO3 / MWCNTs / MnO2 composite material, the characteristic diffraction peaks of BaTiO3 are located at about 2θ=22.17°(100), 31.59°(110), 39.07°(111), 45.30°(200), 50.92°(210), 56.32°(211), 65.86°(220), 70.52°(212), 75.06°(310), 79.22°(311), indicating that it has a high degree of crystallinity. With the increase of MWCNTs filling amount, the graphitization peak in the range of 2θ=25°~30° gradually increases, indicating that the degree of graphitization is improved. Graphitization refers to the orderly arrangement of carbon atoms in a graphite-like layered structure, a process that improves the electrical conductivity and stability of MWCNTs. The graphite peak of the composite material significantly increases with the increase in MWCNTs content. In addition, the degree of graphitization increases with the increase in MWCNTs filling, indicating that MWCNTs not only act as a structural reinforcer but also significantly improve the overall electrical conductivity of the composite material. The high crystallinity and degree of graphitization of BaTiO3 work synergistically in the BaTiO3 / MWCNTs / MnO2 composite material to significantly enhance its functional properties.
[0045] X-ray photoelectron spectroscopy (XPS) was used to further investigate the valence states and chemical compositions of the elements in the BaTiO3 / MWCNTs / MnO2 composites. Figure 2 The presence of C, O, Ti, Mn and Ba elements in the composite material was confirmed. The typical Ba 3d peak was also found in the measured spectrum of BaTiO3 / MWCNTs / MnO2.
[0046] The corresponding TEM and HRTEM images of BaTiO3 / MWCNTs / MnO2 composites are shown in Figure 2. Figure 3As shown in the figure, the presence of BaTiO3, MnO2, and MWCNTs, and the uniform dispersion of BaTiO3 in BaTiO3 / MWCNTs / MnO2, and the BaTiO3 particles did not undergo obvious agglomeration or precipitation, but were closely combined with MnO2 and MWCNTs to form a uniformly distributed composite structure. This indicates that the BaTiO3 / MWCNTs / MnO2 composite material was successfully prepared, and MnO2 showed two distinct shapes in the composite material, namely, urchin-like α-MnO2 nanosheets and rod-like β-MnO2 nanosheets. Its stable internal structure reduces impedance matching and is beneficial to the electromagnetic absorption performance of conduction loss dissipation. The pore structure formed by the highly conductive MWCNTs provides sufficient contact area between the absorbing material and the air medium, promoting the propagation and scattering of electromagnetic waves inside the material. It also promotes impedance characteristics to a certain extent, induces interface polarization, and thus improves the electromagnetic absorption performance of the material.
[0047] The EMW absorption performance of each material is described by RLmin.
[0048] According to the transmission line theory, the reflection loss can be calculated using the relative complex permeability and dielectric constant at a given sample thickness: (1) (2) (3) in, Z in Refers to the normalized input impedance, ε r is the relative complex permittivity ( ε r = ε 0- jε ″), is the relative complex permeability ( µ r = µ ʹ- jµ ″), c is the speed of light in a vacuum, f is the frequency, d is the sample thickness. Z 0 represents air impedance, Z c Represents the characteristic impedance of the material. Z 0 is roughly equal to 1, so Z in / Z A value of 1 to 0 means zero reflection of electromagnetic waves.
[0049] In order to obtain better absorption effect, it is necessary to consider impedance matching. When the impedance characteristics of the material are close to free space, the surface reflection of electromagnetic waves will be small, and the incident electromagnetic waves can be greatly attenuated. Impedance matching coefficient ( Z ) is calculated as follows: (4) The test results are shown in Table 1, where d represents the thickness of the coaxial ring.
[0050] Table 1 EMW absorption performance test results
[0051] The electromagnetic absorption performance of the composite material with a MWCNTs filling content of 10 wt% is enhanced to the greatest extent. When the thickness is 1.9 mm and the frequency is 3.85 GHz, the maximum reflection loss (RLmin) of the composite material reaches -61.44 dB, which may be due to good impedance matching, strong dielectric loss and increased degree of graphitization, leading to increased microwave absorption performance. When the MWCNTs filling content is 5 wt%, the maximum reflection loss of the composite material is -65.11 dB and the thickness is 5.0 mm. At this time, the excessively high wax ratio (8:2) in the composite material leads to lower test results and exhibits lower absorption performance.
[0052] From the above results, it can be seen that compared with pure BaTiO3, BaTiO3 / MnO2 / MWCNTs composites have significant absorption characteristics. In addition, the non-uniform interface formed by MWCNTs in BaTiO3 / MnO2 / MWCNTs composites increases the dielectric loss due to the interface polarization. In addition, the composite of MnO2, BaTiO3 and MWCNTs introduces magnetic components, which enhances the magnetic loss of the composite. Finally, the three-dimensional network structure of the composite induces multiple reflections and scattering of the interface, while reducing impedance matching. By adjusting the electromagnetic parameters and optimizing the impedance matching, an excellent electromagnetic wave absorbing material is obtained. The BaTiO3 / MnO2 / MWCNTs composite has the best wave absorbing performance when the wax ratio is 7:3. When the MWCNTs filling amount is 10 wt% and the thickness is 4.75 mm, the effective absorption bandwidth of the composite is measured to be 4 GHz, and the corresponding maximum reflection loss (RLmin) reaches -74.06 dB. The present application improves the electromagnetic wave absorption performance of the material by regulating the dispersibility of paraffin wax and the conductivity of the composite material.
[0053] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A wave absorbing agent, characterized in that: The invention comprises a BaTiO3 / MWCNTs composite and nano-MnO2 loaded on the surface of the BaTiO3 / MWCNTs composite.
2. The wave absorbing agent according to claim 1, characterized in that: The nano-MnO2 is sea urchin-shaped nano-sheet a-MnO2 and / or nano-rod-shaped β-MnO2.
3. A method for preparing the wave absorbing agent according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Under alkaline conditions, an aqueous solution of Ba(OH)2·8H2O and an alcohol solution of (C4H9O)4Ti are mixed to obtain a mixed solution; the mixed solution is mixed with multi-walled carbon nanotubes and polyethylene glycol and subjected to a hydrothermal reaction to obtain a BaTiO3 / MWCNTs composite; S2. Add KMnO4 to the alcohol solution of the BaTiO3 / MWCNTs composite, perform a secondary hydrothermal reaction, and obtain the absorbent after washing and drying.
4. The preparation method according to claim 3, characterized in that: The temperature of the first hydrothermal reaction is 120-150°C, and the reaction time is 3-5h; The temperature of the secondary hydrothermal reaction is 180-200° C., and the reaction time is 6-10 hours; and / or, The mass ratio of Ba(OH)2·8H2O to (C4H9O)4Ti is (0.25-0.3):(0.25-0.3), and the mass ratio of BaTiO3 / MWCNTs to KMnO4 is 2:(1-1.2).
5. A non-magnetic wave absorbing material, characterized in that: The invention comprises paraffin wax and the wave absorbing agent as claimed in any one of claims 1 to 3.
6. The non-magnetic wave absorbing material according to claim 5, characterized in that: The mass ratio of the paraffin wax to the absorber is (5-8): (2-5).
7. The non-magnetic wave absorbing material according to claim 5, characterized in that: The mass of MWCNTs accounts for 5-20% of the non-magnetic absorbing material.
8. The non-magnetic wave absorbing material according to claim 5, characterized in that: It is a coaxial ring structure, and the thickness of the coaxial ring is 4-5mm.
9. A method for preparing the non-magnetic wave absorbing material according to claim 5, characterized in that: The paraffin wax is mixed with the wave absorber and then pressed.
10. Use of the non-magnetic wave absorbing material as claimed in claim 5 under 2-18 GHz conditions.